Legal Policy Formation of Child-Friendly Districts - Nanarhati Setyamandani, Emei Dwi; Firdausi, Firman; Lestari, Asih Widi (Jurnal Cakrawala Hukum, 2023)
Indonesia will experience a demographic bonus in the next few years. The government predicts that in 2045, the younger generation will reach its peak and this is a potential that must be properly maintained. In line with an international issue that has been ratified, namely children’s rights, the government implemented a program called City/District Suitable for Children (KLA). Currently, not all regions implement KLA due to various factors, but the government’s goal is clear enough to be able to grant this KLA status to every region throughout Indonesia. As of 2022, Probolinggo Regency does not yet have a legal umbrella for KLA, but it has planned the formation of laws and regulations to strongly prepare for this KLA. Through the juridical-normative method this legal void is analyzed using legal political theory. As a result, Probolinggo Regency plans the initiation of KLA regional regulations by looking at legal aspects through Academic Papers and planning aspects through the Regional RPJM. How to cite item: Setyamandani, Emei Dwinanarhati, and Firman Firdausi. â€œLegal Policy Formation of Child-Friendly Districts.â€ Jurnal Cakrawala Hukum 14 no. 3 (2023): 254-264. DOI: 10.26905/idjch.v14i3.9814.